Epidemiology of childhood and adolescent cancer in Bangladesh, 2001–2014. Issue 1 (December 2016) - Hossain, Mohammad; Begum, Mamtaz; Mian, Md; Ferdous, Shameema; Kabir, Shahinur; Sarker, Humayun; Karim, Sabina; Choudhury, Salma; Khan, Asaduzzaman; Khan, Zohora; Karim-Kos, Henrike
Abstract Background Cancer burden among children and adolescents is largely unknown in Bangladesh. This study aims to provide a comprehensive overview on childhood and adolescent cancers and to contribute to the future strategies to deal with these diseases in Bangladesh. Methods Data on malignant neoplasms in patients aged less than 20 years diagnosed between 2001 and 2014 (N = 3143) in Bangladesh was collected by the National Institute of Cancer Research and Hospital and ASHIC Foundation. The age pattern and distribution of cancer types were analysed and the incidence rates were calculated. Results The age-standardised incidence rate was 7.8 per million person-years for children (0–14 years) in the last time period (2011–2014). Retinoblastoma (25 %) and leukaemia (18 %) were the most common childhood cancers. For adolescents (15–19 years), the age-specific incidence rate was 2.1 per million person-years in the same time period. Most common adolescent cancers were malignant bone tumours (38 %), germ cell and gonadal tumours (17 %), and epithelial tumours (16 %). There were more boys affected (M: F ratio 2.0 in children and 1.4 in adolescents) than girls. Conclusion Cancer incidences were lower than expected most likely due to a low level of awareness about cancer among clinicians and the population, inadequate access to health care, lack of diagnostic equipment and incomplete recording of cases. Improvements on different levels should be made to get a better epidemiologic insight and to detect cancer earlier resulting in a better outcome for affected children and adolescents.